Integrating Sustainable Development Goals and Maqâshid al-Syarî‘ah: A Conceptual Framework for Islamic Sustainable Development - Hotman Hotman; Putri Swastika; Diana Ambarwati; Yuyun Yunarti; Riyan Damara Putra (Madania: Jurnal Kajian Keislaman, 2026)
This study aims to develop an integrative conceptual framework between the Sustainable Development Goals (SDGs) and maqâshid al-syarî‘ah within the discourse of Islamic sustainable development. This objective is grounded in the growing criticism that contemporary sustainability discourse remains largely shaped by technocratic and secular-developmentalist assumptions, which often prioritize institutional performance, economic growth, and measurable indicators while overlooking ethical, spiritual, and civilizational dimensions of human well-being. Methodologically, this study employs a qualitative conceptual review using Critical Interpretive Synthesis supported by a PRISMA-inspired literature screening procedure. Literature was collected from Scopus, ScienceDirect, Dimensions, Crossref, and Google Scholar using keywords related to SDGs, maqâshid al-syarî‘ah, Islamic sustainable development, Islamic sustainability, and Islamic environmental ethics. The review focused on peer-reviewed and indexed scholarly publications published between 2021 and 2026. From 86 initially identified records, 41 publications were retained after preliminary screening, and 19 core studies were selected for thematic coding and conceptual synthesis. The findings reveal substantial convergence between SDGs and maqâshid al-syarî‘ah in relation to justice, welfare, environmental stewardship, social sustainability, transcendental accountability, moral responsibility, and civilizational balance. This study concludes that Islamic sustainable development should not be positioned merely as a religious adaptation of global sustainability agendas, but as an ethical-civilizational paradigm capable of enriching and reconstructing contemporary sustainability theory. Studi ini bertujuan untuk mengembangkan kerangka konseptual integratif antara Tujuan Pembangunan Berkelanjutan (SDGs) dan maqâshid al-syarî‘ah dalam wacana pembangunan berkelanjutan Islam. Tujuan ini didasarkan pada kritik yang berkembang bahwa wacana keberlanjutan kontemporer sebagian besar masih dibentuk oleh asumsi teknokratis dan sekuler-pembangunan, yang seringkali memprioritaskan kinerja kelembagaan, pertumbuhan ekonomi, dan indikator terukur sambil mengabaikan dimensi etika, spiritual, dan peradaban dari kesejahteraan manusia. Secara metodologis, studi ini menggunakan tinjauan konseptual kualitatif menggunakan Sintesis Interpretatif Kritis yang didukung oleh prosedur penyaringan literatur yang terinspirasi oleh PRISMA. Literatur dikumpulkan dari Scopus, ScienceDirect, Dimensions, Crossref, dan Google Scholar menggunakan kata kunci yang terkait dengan SDGs, maqâshid al-syarî‘ah, pembangunan berkelanjutan Islam, keberlanjutan Islam, dan etika lingkungan Islam. Tinjauan ini berfokus pada publikasi ilmiah yang ditelaah sejawat dan terindeks yang diterbitkan antara tahun 2021 dan 2026. Dari 86 catatan yang awalnya diidentifikasi, 41 publikasi dipertahankan setelah penyaringan awal, dan 19 studi inti dipilih untuk pengkodean tematik dan sintesis konseptual. Temuan menunjukkan konvergensi substansial antara SDGs dan maqâshid al-syarî‘ah dalam kaitannya dengan keadilan, kesejahteraan, pengelolaan lingkungan, keberlanjutan sosial, akuntabilitas transendental, tanggung jawab moral, dan keseimbangan peradaban. Studi ini menyimpulkan bahwa pembangunan berkelanjutan Islam seharusnya tidak hanya diposisikan sebagai adaptasi agama dari agenda keberlanjutan global, tetapi sebagai paradigma etika-peradaban yang mampu memperkaya dan merekonstruksi teori keberlanjutan kontemporer.